The Effectiveness of the PNM Mekaar Program in Empowering Economically Disadvantaged Women: A Qualitative Study in Salatiga City - Gunarto, Alexandra Nesta Levina; Pramesti, Indah; Saraswati, Birgitta Dian (Gorontalo Development Review, 2026)
The Membina Ekonomi Keluarga Sejahtera (Mekaar) Program, administered by PT Permodalan Nasional Madani (PNM), is a microfinance initiative designed to enhance the economic independence of underprivileged women through access to small-scale financing. This study aims to examine the effectiveness of the PNM Mekaar Program in strengthening the economic capacity of underprivileged women in Salatiga City. A descriptive qualitative approach was employed to explore beneficiaries’ experiences in accessing and utilizing microfinance services. Data were collected through observation, in-depth interviews, and documentation involving eight informants, comprising six Mekaar beneficiaries and two supporting informants, namely an Account Officer (AO) and a member of another Mekaar group. The data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that the Mekaar Program has improved access to financing for underprivileged women through simple administrative requirements and a joint liability system that fosters financial discipline. However, its effectiveness in promoting women’s economic independence remains limited. Most beneficiaries tend to use the financing primarily for household consumption rather than for productive business purposes. Furthermore, limited financial literacy and the absence of structured business mentoring constrain the program’s potential to generate sustainable economic empowerment. These findings suggest that access to microfinance alone is insufficient to strengthen women’s economic empowerment without adequate financial literacy education and systematic business assistance. Therefore, improving beneficiary selection, strengthening financial literacy programs, and providing structured business mentoring are essential to enhance the effectiveness of the Mekaar Program in supporting sustainable economic empowerment among underprivileged women.